Teologia e kantismo nell’estetica di Mariano Campo - Maria Antonietta Spinosa (Aisthesis, 2017)
Through the analysis of Mariano Campo’s (1892-1976) published works and thanks to further insights offered by some unpublished manuscripts, the profile of a philosopher is outlined, whose main interest, throughout his academic and research activity, has been aesthetics. More specifically, Campo has focused on the centrality of feelings to human aesthetic experience: it is through feeling that we experience a transfiguration of reality, which happens paradigmatically when, in front of an artwork, we appreciate it as an integral whole, a totality.